Gender and sustainability - Meinzen-Dick, Ruth S.; Kovarik, Chiara; Quisumbing, Agnes R. (Annual Reviews, 2014)
Sustainability and gender have been prominent on the development agenda since the 1980s, but there has been little systematic study of the links between the two. This review draws on ecofeminist theory, feminist political ecology, intrahousehold literature, and natural resource management case studies and reviews to examine how gender shapes the motives, means, and opportunities for men and women to contribute to sustainability. Particular attention is given to evidence on closeness to nature, focus on conservation, rights to resources, opportunities to exploit resources, and constraints to adoption of sustainable practices. Despite early claims that women are naturally more conserving of resources, the empirical literature, in particular, gives a more mixed and nuanced picture. Conservation is influenced not only by gender but also by a host of tangible and intangible factors, including local ecology, context, and culture, that affect incentives and the ability to adopt sustainable extraction and provision practices.